Periodontal epidemiology: towards social science or molecular biology? - Baelum V, Lopez R. (Blackwell Synergy, 2004)
Terms such as ‘molecular epidemiology’ and ‘genetic epidemiology’ have been coined to depict the change from ‘traditional epidemiology’, concerned with disease determinants at the community or society level, over to ‘modern epidemiology’, which is concerned with determinants operating at the individual level or even below, i.e